PERAN GREEN TRUST MEMEDIASI GREEN PERCEIVED VALUE DAN GREEN PERCEIVED RISK TERHADAP GREEN REPURCHASE INTENTION - Dewi, Sieny Andhika; Rastini, Ni Made (E-Jurnal Manajemen, 2017)
This study aimed to clarify the role of trust mediating green green green perceived value and perceived risk on repurchase intention green products The Face Shop in Denpasar. Collecting data in this study using a questionnaire. The total sample of 100 respondents using non-probability sampling techniques. The analysis technique used in this study is the technique of path analysis (path analysis). Based on the analysis found that the green perceived value and significant positive effect on repurchase intention green. Green perceived risk significant negative effect on the green repurchase intention. Green perceived value has a positive and significant impact on the green trust. Green perceived risk significant negative effect on the green trust. Green trust has a positive and significant impact on the green repurchase intention. Green trusts significantly mediates the effect of perceived value to the green green repurchase intention. Green trusts significantly mediates the effect of perceived risk on the green green repurchase intention.
Keywords: green perceived value; green perceived risk; green trust; green repurchase intention